I support this answer it’s correct I see it ♥️
Answer:
x = -1 and x = 4
Step-by-step explanation:
Firstly solve the quadratic expression of
2x^2-6x-8 = 0....it gives you the two brackets of.....(2x-8)(x+1)=0
then...you equate the two brackets to 0.separately
2x-8 = 0....which gives you...x = 4...as the first solution..then..;
x+1 = 0....which gives you...x = -1...as the second solution
Answer:
don't worry I'm on my way step bro ! where'd you get stuck ?! (;
It appears that for every question missed, it deducts 3 points.
so if Julie missed 6 questions, then she received a : (-3 * 6) = -18